Suppression of Thrust Fluctuation of a New Ironless Tubular Permanent Magnet Synchronous Linear Motor Based on the Halbach Array - Bo Li; Jun-an Zhang; Zhiping Shi; Xiaolong Zhao; Hao Dong (Shock and Vibration)
The air gap magnetic field (AGMF) is the key factor in determining the ironless tubular permanent magnet synchronous linear motor (ITPMSLM). The distortion of its waveform causes thrust fluctuation during the operation of the motor, resulting in poor machining accuracy of the machine tool. To solve this problem, this paper proposes a new chamfered permanent magnet structure (CPMS) to improve its performance. First, the equivalent magnetic charge method is used to analyze the AGMF, and the analytical expressions of the no-load back EMF and thrust of the new motor are obtained. Second, the AGMF of six kinds of CPMS is analyzed by the Fourier coefficient. Taking the minimum harmonic distortion rate as the optimization objective, the CPMS that makes the AGMF waveform reach the best sinusoidal property is obtained and the no-load back EMF and thrust of the new motor are analyzed. Then, the new motor is compared with the ITPMSLM of rectangle permanent magnet structures (RPMS). Finally, according to the CPMS, the test prototype is built and tested under different working conditions. The research results show that when the outer circumference is 45o chamfered, the ratio of permanent magnet thickness h2 to the chamfered thickness h1 is 0.8; the sinusoidal property of AGMF is the best, and this structure can effectively reduce the motor thrust fluctuation rates to less than 0.01%, which verifies the effectiveness of the CPMS in improving the sinusoidal property in the AGMF and restraining the thrust fluctuation of the ITPMLSM.